Enriching player development in women's futsal in Portugal: a narrative account of case examples - Santos, F.; Davids, K.; Carvalho, R.; Rabaça, C.; Queiroz, D. (International Sport Coaching Journal, 2025)
In Portugal, women`s participation in futsal, one of the most popular sports in the country, has increased 85.5% in the last decade, growing from 5,406 to 10,028 female participants. The purpose of this critical commentary is to provide insights on current conditions in women`s futsal in Portugal and what we can learn to improve experiences and opportunities for future generations of players as well as to advance new possibilities for research in this field. Based on the authors` lived experiences and expertise, a narrative account has been developed to showcase athletes` developmental pathways within the female futsal landscape in Portugal as case examples. This article seeks to provide some novel insights across sport systems concerning the processes and mechanisms through which athlete development in women`s sport can be enriched as well as how research can be used to increase equity and social justice. The narrative accounts can be taken to imply that there is the need to increase meaningful opportunities for the development of female futsal athletes through using more contemporary pedagogical strategies and structures by the futsal organizations. These contemporary pedagogical strategies may focus on variables such as improved coach education offerings, increased number of practice sessions per week, and access to modernized facilities and equipment. Moving forward, system-level changes are needed to impact individual-environment relationships more accurately as well as continue to foster the growth of the sport.